The Effect of Life Expectancy, Education, Economic Growth, and Unemployment on Poverty Levels in Probolinggo - Wisanggeni Wahyu Lintang Bayu Segoro; Mohammad Wahed (Global Economics: International Journal of Economic, Social and Development Sciences, 2025)
This study aims to analyze the influence of life expectancy, education, economic growth, and unemployment on the poverty rate in Probolinggo Regency during the period 2010–2023. Poverty is a multidimensional issue that reflects not only economic conditions but also social and demographic aspects, making it essential to examine various determinants simultaneously. The research employs a quantitative method with multiple linear regression analysis, using secondary data obtained from the Central Bureau of Statistics (BPS). By applying this approach, the study seeks to provide a comprehensive understanding of the extent to which these variables contribute to changes in poverty levels. The results reveal that education has a significant and negative effect on poverty, indicating that improvements in educational attainment can directly reduce poverty rates. Better access to quality education equips individuals with skills and knowledge that enhance their employment opportunities and income levels, thereby breaking the cycle of poverty. In contrast, life expectancy, economic growth, and unemployment are found to have no statistically significant impact on poverty levels during the observed period. This suggests that while these variables are important indicators of social and economic well-being, their influence on poverty reduction in Probolinggo Regency is not as strong or direct as that of education. The findings highlight the critical role of education as a key driver in poverty alleviation. They suggest that government policies focusing on expanding access to education, improving learning quality, and ensuring equitable opportunities across different social groups will be more effective in addressing poverty than strategies relying solely on economic growth or labor market interventions. Therefore, this research is expected to serve as a valuable reference for local governments in formulating more targeted, evidence-based, and sustainable development policies that prioritize education as the foundation for long-term poverty reduction.